Professionalization of science management—Comparing formal education and training across Germany, Poland, and Hungary - Müller, Ursula; Toczyski, Piotr; Regös, Nora; Pliszczynska, Olga; Jankovics, Réka (Frontiers in Education, 2022)
Description of the examined questions Our goal is to suggest a working definition of “science management” and to explore and systematically compare study programs related to this area. We focus on science management diplomas, short courses and workshops in three countries: Germany, Poland, and Hungary. What is common and what is different in the approaches to science management in three knowledge societies? Methodology Our method is descriptive and comparative. We use desk research to find out how the programs in science management are structured in three countries and what approaches are specific to them all. Results It became evident that in Germany there are plenty of offerings in terms of specialized study programs and short courses. There is a certain dynamic regarding the interconnectedness of research fields and the institutionalization of education and training. This leads to self-reinforcing dynamics concerning professionalization of science management, although science managers still can be hardly labeled as professionals. In Poland and Hungary there is still not much momentum to the process of professionalization, although first efforts are made. Programs such as European Research Area (ERA)-Fellowship might contribute to the evolution of multi-lateral networks between these countries and Germany. The awareness and broad understanding of science management might spread also in Central and Eastern European countries. Conclusion We conclude that the impact on the professionalization of science managers in Germany, Poland, and Hungary is unequal. Concerning training and education in Poland and Hungary, this article might be one step toward showing the broadness inherent to the concept of “science management.” It might stimulate more people in Central and Eastern European countries to think about this, to generate knew knowledge and to teach their insights within newly established study programs or short courses.